Kinetic Energy and Vorticity Perspectives of the Rapid Development of an Explosive Extratropical Cyclone Over the Northwest Pacific Ocean in February 2018 - Wang, Hui; Du, Mengjiao; Sun, Chenghu; Zhang, Bo (Frontiers in Earth Science, 2022)
Explosive extratropical cyclones (EECs) have long been a research focus for the meteorological society as they often cause serious economic losses and casualties. However, after a long period of research, there still remain some knowledge gaps about their rapid development. In this article, we conducted the first study by using both vorticity and kinetic energy (KE) budgets simultaneously on a typical EEC, which was the strongest EEC that affected the coastal areas of China in the last three years, to further the understanding of the mechanisms governing its rapid enhancement in rotation and wind speed. The vorticity budget shows that, the lower-level convergence related vertical stretching and the vertical transport of vorticity acted as the most and second most favorable factors for the increase in the cyclone’s cyclonic vorticity, respectively, which were different from those findings based on the Zwack-Okossi vorticity budget. In contrast, the horizontal transport of vorticity and tilting mainly decelerated the EEC’s development. Energetics features governing the rapid wind enhancement of the EEC were shown for the first time. It is found that, the work on the rotational wind by the pressure gradient force and the net-import transport of KE by the rotational wind contributed the largest and second largest to the cyclone’s increase in wind speed. In contrast, the upward transport of KE and the cyclone’s displacement mainly acted in an opposite way. Analysis based on the Green's theorem and rotational wind shows that the enhancement of the EEC’s rotation and wind speed were linked to each other solidly.